2014
DOI: 10.1590/bjpt-rbf.2014.0047
|View full text |Cite
|
Sign up to set email alerts
|

Muscular performance characterization in athletes: a new perspective on isokinetic variables

Abstract: Background: Isokinetic dynamometry allows the measurement of several variables related to muscular performance, many of which are seldom used, while others are redundantly applied to the characterization of muscle function. Objectives: The present study aimed to establish the particular features of muscle function that are captured by the variables currently included in isokinetic assessment and to determine which variables best represent these features in order to achieve a more objective interpretation of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
0
26
0
3
Order By: Relevance
“…Also, in the isokinetic muscle strength evaluation, the acceleration and deceleration time values are related, among other factors, to muscle activation [28,36]. Acceleration time indicates the neuromuscular ability to move a limb from rest position to predetermined isokinetic speed, and may be an indicator of neuromuscular capacity to develop torque quickly; lower values of this variable may represent higher muscle fibre recruitment capacity of tested muscles [37]. Moreover, deceleration time represents the total time to reduce isokinetic velocity at the end of range of motion, and indicates the neuromuscular ability to control the movement eccentrically [38].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the isokinetic muscle strength evaluation, the acceleration and deceleration time values are related, among other factors, to muscle activation [28,36]. Acceleration time indicates the neuromuscular ability to move a limb from rest position to predetermined isokinetic speed, and may be an indicator of neuromuscular capacity to develop torque quickly; lower values of this variable may represent higher muscle fibre recruitment capacity of tested muscles [37]. Moreover, deceleration time represents the total time to reduce isokinetic velocity at the end of range of motion, and indicates the neuromuscular ability to control the movement eccentrically [38].…”
Section: Discussionmentioning
confidence: 99%
“…Peak torque has been the most widely reported and discussed variable characterizing muscular performance; however, it is limited to the description of torque generation capacity at a single point in the range of motion [42,43]. Conversely, the variable muscular work provides information on the ability of the muscle to generate torque throughout the entire range of motion [44]. Within that context, individuals able to generate high peak torque do not systematically exhibit the greatest values for muscular work.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Amaral, et.al. [44] propose that these two variables best rep-resent the construct of torque generation capacity of skeletal muscle, allowing an accurate examination of muscle performance to identify specific deficits, or to assess the results of interventions. Our study showed a decrease of ̴30 % not only on the isokinetic peak torque (60 °/s) but also on muscular work 48h after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, in contrast to typical isovelocity dynamometer testing, natural movements such as those listed above are characterized by limb acceleration, and a recent factor analysis study found that the capacity to accelerate a limb is one of five factors that characterize neuromuscular performance of athletes. 10 Accordingly, isometric and concentric RTD likely represent different aspects of explosive torque production, but to date very little is known about the influence of varying accelerations on torque production during maximum voluntary explosive concentric contractions.…”
Section: Introductionmentioning
confidence: 99%